2018
DOI: 10.1134/s0006297918080060
|View full text |Cite
|
Sign up to set email alerts
|

Essential Light Chains of Myosin and Their Role in Functioning of the Myosin Motor

Abstract: This review summarizes current data on the structure and functions of myosin essential light chains (ELCs) and on their role in functioning of the myosin head as a molecular motor. The data on structural and functional features of the N-terminal extension of myosin ELC from skeletal and cardiac muscles are analyzed; the role of this extension in the ATP-dependent interaction of myosin heads with actin in the molecular mechanism of muscle contraction is discussed. The data on possible interactions of the ELC N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Human MLC molecules exist mainly as essential catalytic subunits and regulatory/phosphorylatable subunits, i.e., as fast MLC1/MLC3 (P05976; MYL1 gene) and fast MLC2 (Q96A32; MYLPF gene) or slow MLC1 (MLC3) (P08590; MYL3 gene) and slow MLC2 (P10916; MYL2 gene) isoforms. The combination of various MyHC and MLC subunits form a very large number of hexameric iso-myosins in the sarcomere [92,121,122]. In contrast, human filamentous F-actin polymers in developing and mature fibres consist of only two G-actin isoforms, i.e., cardiac alpha-actin (P68032; ACTC1 gene) and muscle alpha-actin (P68133; ACTA1 gene).…”
Section: Top-down Proteomics Of Contractile Proteins From Skeletalmentioning
confidence: 99%
“…Human MLC molecules exist mainly as essential catalytic subunits and regulatory/phosphorylatable subunits, i.e., as fast MLC1/MLC3 (P05976; MYL1 gene) and fast MLC2 (Q96A32; MYLPF gene) or slow MLC1 (MLC3) (P08590; MYL3 gene) and slow MLC2 (P10916; MYL2 gene) isoforms. The combination of various MyHC and MLC subunits form a very large number of hexameric iso-myosins in the sarcomere [92,121,122]. In contrast, human filamentous F-actin polymers in developing and mature fibres consist of only two G-actin isoforms, i.e., cardiac alpha-actin (P68032; ACTC1 gene) and muscle alpha-actin (P68133; ACTA1 gene).…”
Section: Top-down Proteomics Of Contractile Proteins From Skeletalmentioning
confidence: 99%
“…4 . MYL4 and MYL3 are atrial- and ventricular-specific essential light chains respectively [ 7 ]. It's notable that MYL4 mutation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are two types of light chains in the myosin chaperone, the essential light chain (ELC) and the regulatory light chain. MYL4 is an atrial-specific ELC that is necessary for ATPase activity of the myosin head and also for actin binding [ 7 ], a process that directly determines motor function.…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the C-termini of PfELC as well as TgELCs are partially disordered, although to a different degree, and constitute the typical calmodulin fold only upon binding to the MyoA neck domain. This seems plausible because no structure of essential light chain has been solved in isolation so far and it has been suggested that they are disordered in the unbound state [36].…”
Section: Discussionmentioning
confidence: 99%